METODE BERMAIN KOOPERATIF DALAM MENINGKATKAN ANTUSIAS BELAJAR ANAK USIA DINI PADA MASA COVID-19 - Rakhman, Anita; Alam, Syah Khalif (Abdimas Siliwangi, 2022)
This community service activity is motivated by the large number of young children who are less enthusiastic about taking online learning at home. This is a challenge for PAUD teachers in improving their ability to provide creative and fun learning through cooperative play methods. This activity aims to 1) Provide an overview of cooperative play methods in increasing early childhood learning enthusiasm during the Covid-19 period. 2) provide information about the benefits of cooperative play methods in increasing early childhood learning enthusiasm during the Covid-19 period. To achieve this goal, activities in the form of counseling and conducting question and answer sessions with Webinar participants were carried out. The results of this activity show that participants / teachers are motivated to implement cooperative play methods in increasing early childhood learning enthusiasm during the Covid-19 period.